ҚАРАҚАЛПАҚ ХАЛЫҚ НАҚЫЛ-МАҚАЛЛАРЫ ТИЛИНДЕ «ТОН» КИЙИМ-КЕНШЕК АТАМАСЫНЫҢ ҚОЛЛАНЫЛЫЎЫ - Юсупова, Б.Т. (SCIENCE and SOCIETY, 2024)
The article examines one of the terms of the national clothing of the people - the tone in the language of Karakalpak folk proverbs and the features of its types. Among the Karakalpak clothes, tone was preserved in proverbs as the name of the most honorable and noble clothing; they inherited the wisdom of this national clothing. In the article, the features of the use of “tone” are compared with the use in the language of other genres of folklore - folk songs, sayings, as well as other works of art.
Keywords: proverbs; expressions; sayings; names and types of clothes